KARAKTER HIBRID ACACIA (Acacia mangium x A. auriculiformis) BERDASARKAN VIABILITAS BENIH, KEMAMPUAN BERTUNAS DAN BERAKAR STEK - Sri Sunarti; Muhammad Na'iem; Eko Bhakti Hardiyanto; Sapto Indrioko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2012)
The first generation of Acacia hybrid between A. mangium and A. auriculiformis potential to be developed for plantation because of its superiority. The superiority of hibrid Acacia were fast growth, straight bole, light branching, more tolerant to pest/disease attack and better wood property than the parent trees. The only way to maintain their superiority is to propagate it vegetatively. The objective of the research was to observed characteristics of hibrid Acacia based on seed viability,sprouting and rooting ability. Materials used in this study were collected seed from control pollination at breeding garden which verified by molecular marker. The result showed that the character of seed viability on hybrid Acacia was still low (48.1%) meanwhile the sprouting and rooting ability were 16.5 ± 0.7 shoots and 78,4% respectively.